Powtoon Animation Video Based on Contextual Approach in Elementary School Mathematics Learning - Sari, Ni Kadek Candra Permata (MIMBAR PGSD Undiksha, 2022)
The lack of media or supporting tools in teaching and learning activities and the lack of material presented make the learning process less meaningful. It can cause the learning process to be less effective, and students will become less familiar with the material being taught. This study aims to develop learning media in animated Powtoon videos based on a contextual approach to learning the circumference and area of ​​a triangle for fourth-grade elementary school students. This research is development research that uses the ADDIE research model. The method used in this study is a questionnaire with the provision of an assessment sheet instrument given to 2 lecturers as material experts, two lecturers as media experts, two teachers as practitioners, and five students. The instrument used in this study is a rating scale. The data that has been obtained will then be analyzed using the Mean formula to get an average media validity score. The results of the average value of the validity of the Powtoon animation video media based on the contextual approach from material experts was 4.83 with very good qualifications, from media experts 4.83 with very good qualifications, from practitioners 4.83 with very good qualifications, and student response of 4.75 with very good qualifications. So it can be said that the Powtoon animation video learning media based on the contextual approach developed in learning the circumference and area of ​​a triangle is valid and can be used in learning for fourth-grade elementary school students.